2018
DOI: 10.2106/jbjs.oa.18.00004
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Overlapping Surgery Is Safe in Total Knee and Hip Arthroplasty

Abstract: Background:Overlapping surgery occurs when a surgeon performs 2 procedures in an overlapping time frame. This practice is commonplace in the setting of total joint arthroplasty and is intended to increase patient access to experienced surgeons, improve efficiency, and advance the surgical competence of surgeons and trainees. The practice of overlapping surgery has been questioned because of safety and ethical concerns. As the literature is scarce on this issue, we evaluated the unplanned hospital readmission a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 12 publications
0
46
0
Order By: Relevance
“…Exclusion criteria consisted of (1) case reports or series with ,10 patients, (2) review articles, (3) expert opinions, (4) letters to editors, (5) instructional course lectures, (6) studies involving animals or cadavers or in vitro investigations, (7) book chapters, (8) abstracts from scientific meetings, (9) unpublished reports, (10) studies in which no subjects underwent TJA, (11) studies which analyzed different surgeries in conjunction with TJA, (12) studies that did not include TJAs done in an overlapping surgery setting and (nonoverlapping surgery) setting for direct comparison, and (13) non-English language publications. A cross-reference search of the selected articles was also done to obtain other relevant articles.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Exclusion criteria consisted of (1) case reports or series with ,10 patients, (2) review articles, (3) expert opinions, (4) letters to editors, (5) instructional course lectures, (6) studies involving animals or cadavers or in vitro investigations, (7) book chapters, (8) abstracts from scientific meetings, (9) unpublished reports, (10) studies in which no subjects underwent TJA, (11) studies which analyzed different surgeries in conjunction with TJA, (12) studies that did not include TJAs done in an overlapping surgery setting and (nonoverlapping surgery) setting for direct comparison, and (13) non-English language publications. A cross-reference search of the selected articles was also done to obtain other relevant articles.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Four studies defined overlapping surgery as a TJA surgery that was preceded or followed by another joint replacement procedure (primary or revision) in a different OR, with a scheduled time overlap of at least 30 minutes between the cases. 9,[11][12][13] One of these studies reported that the interquartile range for the overlap time was between 60 and 104 minutes. 11 One study defined overlapping surgery as that in which the surgeon completed the critical portions of a case and then transitioned directly to a second room for the critical portions of the next procedure.…”
Section: Overlapping Surgery Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the practice of overlapping surgeries, which consists of a main surgeon coordinating two or more operating rooms at the same time, has been the subject of extensive debates between the medical community and society, [1][2][3] besides gaining more and more space in the main journals around the world. [4][5][6][7][8] This practice, although not legally permitted in Brazil, is quite common in academic medical centers, being essential for the training of residents and presenting benefits such as reduced waiting time for patients to undergo surgery, decrease in surgical costs, optimization of hospital revenues, in addition to promoting the development of skills and autonomy of resident doctors and increasing the number of doctors involved in patient care.…”
Section: Introductionmentioning
confidence: 99%